Damage detection in noisy environments based on EMI and Lamb waves: A comparative study - Campeiro, Leandro Melo [UNESP]; Budoya, Danilo Ecidir [UNESP]; Baptista, Fabricio Guimarães [UNESP] (SAGE Publications, 2022)
Structural health monitoring (SHM) systems have shown the potential to detect damage in various types of structures, thus increasing safety and reducing maintenance costs. Among the damage detection methods are those that use small piezoelectric transducers attached to the monitored structure, such as the electromechanical impedance (EMI) and Lamb waves methods. Although both methods have shown to be effective in detecting structural damage, external disturbances such as noise can alter the signals from piezoelectric sensors in real applications and prejudice the correct diagnosis of the monitored structure. Therefore, this paper presents a comparative analysis of the performance of EMI and Lamb waves methods in noisy environments, which is a condition commonly found in real structures. The obtained results add value to the SHM field by allowing to know the tradeoff in choosing the appropriate method regarding the detection, quantification, and location of structural damage under noise conditions. Experimental tests were performed on aluminum structures to assess the effectiveness of both techniques to detect, quantify, and locate structural damage under noise of different intensities. The experimental results show that each technique has different characteristics in terms of effectiveness in detecting, quantifying, and locating damage under noise effects.
Keywords: damage detection; electromechanical impedance; Lamb waves; noise; Piezoelectric transducers